Development of Quizlet Platform-Based Learning Media for Middle School Students' Understanding of Arabic Vocabulary - Annisa Hanin Larenzi; Syarifudin Basyar; Fachrul Ghazi; Tamer Sa’ad Ibrahim Khedr (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Quizlet platform-based learning media is an interactive learning media that can be used in the Arabic language learning process, especially vocabulary. This research is based on the problems students encounter when learning Arabic, especially vocabulary. Students have difficulty learning Arabic because they consider Arabic to be a difficult subject and the lack of learning media used by teachers means that students lack enthusiasm in the learning process. This research is research and development research (R&D), namely research activities that begin with research and end with development. This research uses a mixed methods approach and the Hannafin and Peck development model, which consists of three phases: the first phase is need assessment, the second phase is design, and the third phase is development and implementation. This research aims to determine the feasibility of learning media based on the researcher' developed Quizlet platform. The data in this research are in the form of observations, interviews, questionnaires, and documentation. The subjects of this research are students in class 8F of the Insan Mulia Islamic Boarding School in Pringsewu Lampung. The following are the research steps carried out by the researcher: 1. The first phase is needs analysis, the researcher carries out direct observations and personal interviews with Arabic teachers. 2. The second phase, namely design, the researcher designed an Arabic language learning media design based on the Quizlet platform. 3. The third phase, namely development and implementation, researcher developed learning media based on the Quizlet platform and validate it by experts. Researcher conducted product feasibility tests. Several validators validated these: two were learning material experts, two were learning media experts, and one was an educational practitioner expert. Researcher obtained research results with validation results by experts with very good grades, including: 91% by material experts, 94% by learning media experts, and 90% by education practitioner experts. Therefore, Arabic language learning media based on the Quizlet platform developed by researchers is suitable for use in Arabic language learning, especially vocabulary.